Improving Students’ Writing Skills Through ICT-Based Learning: A Classroom Action Research - Helen Moneka (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Writing remains one of the most demanding productive skills for EFL learners in Indonesian secondary schools, where instruction has traditionally been teacher-centered and insufficiently supported by meaningful technology integration. This Classroom Action Research (CAR) study examines how ICT-based learning affects the writing skills of eleventh-grade students at SMA Negeri 2 Pagar Alam, South Sumatra. A mixed-methods design was applied across two action research cycles, each covering three instructional meetings followed by a writing assessment. The 25 student participants were evaluated on five writing componentscontent development, organization, grammar, vocabulary, and mechanics using an analytic rubric adapted from Jacobs et al. (1981). Quantitative data came from pre-test and post-test scores, while qualitative data were drawn from observation checklists and field notes. Results showed that the overall class mean rose from 57.44 at pre-test to 67.70 after Cycle I and reached 77.22 after Cycle II, a total gain of 19.78 points. The student passing rate climbed from 12% at pre-test to 80% at the conclusion of Cycle II, surpassing the 75% threshold required for the study to be considered successful. Qualitative findings pointed to stronger student participation, more consistent use of ICT tools, and a gradual shift toward process-oriented writing behavior. These outcomes suggest that a carefully scaffolded, multi-tool ICT approach integrating Google Docs, Canva, and Grammarly within a process writing framework can meaningfully improve EFL writing competence at the secondary school level.